2018
DOI: 10.1021/acsnano.8b05512
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Nanoparticle Interaction as a Design Principle in the Development of a Durable Ultrathin Universal Binary Antibiofilm Coating with Long-Term Activity

Abstract: Bacterial attachment and biofilm formation pose major challenges to the optimal performance of indwelling devices. Current coating methods have significant deficiencies including the lack of long-term activity, easy of application, and adaptability to diverse materials. Here we describe a coating method that could potentially overcome such limitations and yield an ultrathin coating with long-term antibiofilm activity. We utilized the interaction between polydopamine (PDA) nanoaggregates/nanoparticles and ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 54 publications
2
80
0
Order By: Relevance
“…The molecular weight of PDMA was crucial to form a coating with strong antibiofilm activity. The PDMA with ultrahigh molecular weight exhibits its unique characteristics as it can control the self‐assembly of polydopamine (PDA) nano‐aggregates [ 27 ] formed during the polymerization of dopamine and resulted in a stable, thin, and uniform coating with PDMA chains enriched on the surface of diverse substrates irrespective of their surface chemistry or morphology (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular weight of PDMA was crucial to form a coating with strong antibiofilm activity. The PDMA with ultrahigh molecular weight exhibits its unique characteristics as it can control the self‐assembly of polydopamine (PDA) nano‐aggregates [ 27 ] formed during the polymerization of dopamine and resulted in a stable, thin, and uniform coating with PDMA chains enriched on the surface of diverse substrates irrespective of their surface chemistry or morphology (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously developed a water‐based, simple one‐step dip coating approach based on mussel‐inspired chemistry and coassembly with hydrophilic ultrahigh molecular weight poly( N,N ‐dimethylacrylamide) (uhPDMA) under ambient conditions. [ 27 ] It was found that the polymer chemistry and molecular weight of hydrophilic polymer is crucial to form an antifouling coating against bacterial adhesion over the long term. In this study, we investigated the mechanism of formation, performed extensive surface characterization of the coating, applied the self‐limiting thin antiadhesive coating on diverse clinically used catheter materials of different interfacial properties, and the scalability of the coating process to human‐sized catheters.…”
Section: Introductionmentioning
confidence: 99%
“…The former mainly employs surface modifications, bactericidal coatings or anti-adhesive compounds as physical barriers [ 9 , 10 ], and the latter involves antimicrobial agents that kill or inhibit the growth of microorganisms [ 11 ]. Despite the advancements in the development of antimicrobial and anti-biofilm materials, coating techniques bear significant deficiencies, including the lack of long-term activity and stability, lack of coating adaptability to diverse materials, easy production and simple application [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the specific building blocks and the assembly conditions, various nano-structured morphologies, including fibrils, tubes, sheets, tapes, spheres, vesicles and hydrogel matrices, can be formed in vitro, allowing for distinctive functional possibilities [ 28 , 30 , 31 , 32 , 33 , 34 , 35 ], mainly in tissue engineering [ 36 , 37 , 38 , 39 ], regenerative medicine [ 40 ], cell culture [ 41 , 42 , 43 , 44 ], drug delivery [ 36 , 39 , 45 , 46 , 47 , 48 , 49 ], bio-imaging [ 50 , 51 ] and fabric functionalization [ 52 ]. Coatings based on self-assembled peptides, primarily for antibacterial purposes, have been recently reported [ 5 , 12 , 13 , 21 , 53 , 54 , 55 , 56 ]. The self-assembly of the tri-peptide DOPA-Phe(4F)-Phe(4F)-OMe into an antifouling coating by the dip-coating technique was reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation